1982
DOI: 10.1097/00000658-198201001-00006
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Patients with Clinical Stage I Melanoma of Intermediate Thickness (1.51–3.99 mm)* A Conceptual Model for Tumor Growth and Metastasis

Abstract: Fourteen variables were tested for their ability to predict visceral or bony metastases in 177 patients with clinical Stage I melanoma of intermediate thickness (1.51 - 3.39 mm). A Cox multivariate analysis yielded a combination of four variables that best predicted bony or visceral metastases for these patients: 1) mitoses greater than 6/min 2 (p = 0.0007), 2) location other than the forearm of leg) p = 0.009, 3) ulceration width greater than 3 mm (p = 0.04), 4) microscopic satellites (p = 0.05). The overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(62 citation statements)
references
References 22 publications
4
56
1
1
Order By: Relevance
“…[1][2][3][4][5][6][7] Age of the patient and pathological features, such as ulceration, microsatellitosis, lymphatic invasion, and extensive regression, may likewise adversely affect prognosis. [1][2][3][4][5][6][7] The presence of regional or distant metastasis is the most powerful prognostic factor available 1,[8][9][10][11][12] and takes precedence over primary tumor characteristics. Melanoma has been shown to metastasize to the regional lymph nodes in a systematic fashion, with "skip" metastases within a nodal group being rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] Age of the patient and pathological features, such as ulceration, microsatellitosis, lymphatic invasion, and extensive regression, may likewise adversely affect prognosis. [1][2][3][4][5][6][7] The presence of regional or distant metastasis is the most powerful prognostic factor available 1,[8][9][10][11][12] and takes precedence over primary tumor characteristics. Melanoma has been shown to metastasize to the regional lymph nodes in a systematic fashion, with "skip" metastases within a nodal group being rare.…”
Section: Discussionmentioning
confidence: 99%
“…13 The historical experience with elective lymph node dissection for patients with intermediate-or high-risk primary cutaneous melanomas has shown that approximately 20% of clinically node-negative patients harbor microscopic lymph node metastases in the regional draining lymph node beds. 7,13,14 It has recently become possible to identify this subset of patients with occult microscopic regional lymph node involvement 14 without subjecting all patients at risk to a lymph node dissection, which involves the formal resection of all lymph nodes in a regional basin. The use of lymphoscintigraphy for presurgical mapping enables the qualified surgeon to STUDY identify for selective biopsy the few anatomical lymph nodes at risk for metastatic spread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the group with a thickness of 1.5-2.99 mm there were two out of nine (22%) cases with positive sentinel node compared with 7 out of 26 (26%) in the group with thickness above 3.0 mm. This is perhaps not surprising as the proponents of elective lymphadenectomy claim that the risk of developing regional node disease increases with the thickness of the primary melanoma and propose that elective lymph node dissection is beneficial in those patients with intermediate thickness tumour (1.5-4.0 mm) (Das Gupta, 1977;Day, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Therapy and prognostication depend on the pathologist's ability to accurately identify by light microscopy the vertical growth phase, as it defines the point in lesional evolution when a melanoma acquires the ability to metastasize and to kill the patient. [12][13][14][15] Radial vs Vertical Growth Phase…”
Section: Introduction and Clinical Featuresmentioning
confidence: 99%